Pertanggungjawaban Pidana Terhadap Suami Pelaku Penelantaran dan Penganiayaan Psikis Terhadap Istri Ditinjau Dari Undang-Undang Nomor 23 Tahun 2004 Tentang Penghapusan Kekerasan Dalam Rumah Tangga - Ahmad (KRTHA BHAYANGKARA, 2023)
The high rate of domestic violence prompted the government to promulgate a law that specifically regulates domestic violence, so that Law Number 23 of 2004 concerning the Elimination of Domestic Violence was born. Violence that occurs against women is often perpetrated by husbands, therefore in this writing the issue that will be discussed is how criminal responsibility is towards husbands who are perpetrators of neglect and psychological abuse of wives in terms of Law Number 23 of 2004 concerning the Elimination of Domestic Violence. From the research conducted, it can be concluded that violence against women violates and prevents women from enjoying their human rights and basic freedoms, so that there must be a legal action to protect wives or women from all kinds of violence they experience.